To solve the quadratic equation \(x^2 - 12x + 36\) using the perfect square trinomial pattern, we can rewrite the equation in the form \((x - a)^2 = 0\):
-
Identify the perfect square trinomial: \(x^2 - 12x + 36\) can be factored as: \[ (x - 6)^2 \]
-
Set the equation equal to zero: \[ (x - 6)^2 = 0 \]
-
Solve for \(x\) by taking the square root of both sides: \[ x - 6 = 0 \]
-
Therefore: \[ x = 6 \]
So the solution to the quadratic equation \(x^2 - 12x + 36 = 0\) is: \[ x = 6 \]
The appropriate response is: x = 6.